Yazıdan sanata, inançtan düşünceye (İstanbul)
xix, 395 sayfa
Keywords: “Anadolu Yarımadası, Doğu ile Batı’nın kesiştiği; iklimiyle, bereketli toprakları ve doğal zenginlikleriyle insanlık tarihinin en görkemli medeniyetlerine ev sahipliği yapmış bir coğrafyadır. Doğa ile insanın kadim birlikteliği bu topraklarda farklı kültürlerin ve geleneklerin sürekliliğini sağlamış, yerel kimliklerin oluşumuna zemin hazırlamıştır. Tarih boyunca dışarıdan gelen kavimler Anadolu’nun ruhuyla bütünleşmiş, kendi kültürlerini yerelle harmanlayarak yeni ve özgün uygarlıklar yaratmışlardır. Kitap, 2011 yılında başlayan Tüpraş Anadolu Uygarlıkları Serisi’nden süzülerek oluşturulmuş özel bir seçkidir. Seri kapsamında yayımlanan Urartular, Frigler, Hititler, Pergamon, Lykialılar, Persler, Assurlular, Hellenistik ve Roma Dönemi, Karialılar, Bizanslılar, İonialılar ve Pamphylialılar olmak üzere 12 kitabın her birinden seçilen makalelerle derlenen bu eser, bir yandan akademik derinlik sunarken, diğer yandan Anadolu uygarlıklarını tarihsel bağlamları içinde bütüncül bir perspektifle değerlendirmemize olanak sağlıyor.” -- “Due to its favorable climate, geographic location, fertile lands, and natural riches, Anatolian peninsula - at the intersection of the East and the - West has been a home to many magnificent civilizations in human history. The ancient and enduring bond between nature and humanity has led to the emergence and resilience of diverse cultures and traditions that paved the path for the formation of local identities in these lands. Throughout the ages, tribes coming to Anatolian from the outside were imbued with the Anatolian spirit and, thus, they created new and original civilizations blending their own cultures with the local and indigenous ones. This book contains a special selection of chapters distilled from the Tüpraş Anatolian Civilizations Series, which commenced in 2011. This compiled volume of selected articles from each of the twelve books in this series Urartians, Phrygians, Hittites, Pergamon, Lycians, Persians, Assyrians, Hellenistic and Roman Period, Carians, The Byzantine Period, Ionians, and Pamphylia offers not only the depth of expert scholarship on each period of focus, but also allows us to appreciate Anatolian civilizations in their historical context within a holistic perspective.” --